Effect of two diets on the fecundity of ablated and non-ablated female of Macrobrachium amazonicum - Gisele Lima Rocha; Tiago Viana da Costa; Noédson de Jesus Beltrão Machado; Tomaz Lima Gualberto; José Cláudio Bezerra Muniz Júnior (Acta Scientiarum. Animal Sciences, 2023)
Macrobrachium amazonicum is a species of freshwater shrimp of great importance for aquaculture and to know its reproductive potential, through the study of its fertility is necessary. Therefore, this study aimed to evaluate the effect of two different diets on the reproductive performance of the species, whether or not adopting the ablation procedure. The experiment was carried out in a completely randomized design in a 2 x 2 factorial arrangement, with two types of feed (inert and fresh) and two conditions (ablated and non-ablated females), using six replicates per treatment. After 10 days of spawning, the eggs were removed and counted in their entirety. For each female, three spawns were obtained, totaling 72 samples. The fertility rate, the interval between spawning and the weight gain of the females were analyzed. There was no interaction between the studied factors, except for weight gain, in which ablated females that received fresh feed gained up to three times more weight than non-ablated females. Females that received fresh feed obtained higher fertility (1,373.9 eggs) than those that received only inert feed (1,084.1 eggs). The interval between spawns was 1.6 days shorter in ablated females.